River basin planning and management - Abu-Zeid, Mahmoud A.; Biswas, Asit K. (Calcutta : Oxford University Press, 1996)
Selected papers presented at the Nile 2002 Conference held in Aswān, Egypt on 1-6 Feb. 1993.
Includes bibliographical references and index.
Moklesur
Keywords: Water resources development -- Nile River Watershed -- Congresses; Watershed management -- Nile River Basin -- Congresses; Nile River -- Regulation -- Congresses